Leadership Coaching in the Fourth Industrial Revolution - Forbes, Raymond L. (Advances in Social Sciences Research Journal, 2024)
Today’s world of extraordinary change follows a long history of technology-driven industrial revolutions. Author Alvin Toffler eloquently identified, categorized, and named the first three of them: Agricultural, Industrial, and Informational. Likening these revolutions to major waves of change, Toffler also described their impact on the social, political, economic and environmental ethos of the times in which they occurred. Recently, a number of knowledgeable commentators have suggested that we are now on the cusp of a fourth industrial wave. This large-scale transformational groundswell is being propelled by a dramatic acceleration in the rate of change itself. It is characterized by major discoveries in Artificial Intelligence, biology, materials science, and neuroscience. In order to remain effective and viable, Leadership Coaching will need to successfully adapt to this virtual thunderstorm of change. This paper will provide background on the preceding waves of industrial change and provide some preliminary glimpses into the just dawning fourth industrial wave. This work will also delve into the potential impact of the newest wave on the leadership coaching profession, describe a few of the latest techniques being introduced, consider the wave’s possible impact on the important work of coaches, and suggest a set of options for the future.